KOMPARASI KREATIVITAS PENCIPTAAN GERAK TARI ANTARA SISWA LAKI-LAKI DAN PEREMPUAN KELAS XI SMA - Kharimah, Siti; Ismunandar, Ismunandar; Istiandini, Winda (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractSMA Taruna Bumi Khatulistiwa is a boarding school that has a semi-military education system, so in this school of cultural arts learning, especially dance is rarely held. So that teachers often difficult to see the level of creativity of male and female students, especially in the field of dance. Therefore, this study aims to determine the difference of creativity ability of dance movement between male and female students in the learning of dance class XI in SMA Taruna Bumi Khatulistiwa Kubu Raya. By using gender theory, that is the apparent difference between men and women when viewed from values and behavior. This study uses a comparative approach and the method used in this study is a survey method of personal interview type. The sample in this research is class XI Sain and Social which amount to 50 male students and 50 female students. Data collection techniques used are direct observation techniques and measurement techniques. While the technique used to analyze the data is the analysis desktiptif and statistics with see the average and ujit t. Based on the result of data analysis about creativity ratio of dance movement between male and female students of grade XI of SMA Taruna Bumi Khatulistiwa Kubu Raya by comparing between male and female students shows obtained by 31,48. The with 5% significance level for two sides with df = 100 then obtained by 1.98. Since the value of >, then Ho is rejected. That is, there are significant differences between male and female students in the creation of dance moves.Keywords: Comparison , Creativity, Dance Movement Creation